Peran Hukum dalam Mencegah dan Menangani Human Trafficking Perempuan dan Anak untuk Eksploitasi Seksual Komersil di Kelurahan Meruyung Kota Depok - Kayus Kayowuan Lewoleba; Mulyadi Mulyadi; Yuliana Yuli Wahyuningsih (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Human trafficking, or the trafficking of human beings, especially women and children for commercial sexual exploitation, is a serious problem with widespread impacts, particularly on women and children as vulnerable groups. Efforts to prevent and address these cases require an effective legal framework as a foundation for protecting human rights and guaranteeing justice. This community service activity aims to educate and educate the community in Meruyung Village, Depok City, about the role of law in preventing and addressing human trafficking. The methods used include outreach, interactive discussions, and case study simulations to increase community awareness and ability to recognize potential human trafficking and prevent it. The expected outcome of this activity is an increased public understanding of the national legal framework, such as Law Number 21 of 2007 concerning the Eradication of the Crime of Human Trafficking, and the role of law enforcement officers in protecting victims and prosecuting perpetrators. In addition, this activity aims to encourage active community participation in preventing human trafficking through strengthening social networks and reporting cases. Thus, the Meruyung Village community is expected to become more responsive to the issue of human trafficking and contribute to creating a safe environment free from commercial sexual exploitation. In addition to legal and educational approaches, collaboration between various parties is also key to eradicating human trafficking. Local governments, civil society organizations, educational institutions, and law enforcement officials need to work together to build an integrated protection system. This synergy can be realized through training for community cadres, establishing complaint posts at the sub-district level, and involving community and religious leaders as agents of change. With a comprehensive, community-based approach, human trafficking prevention efforts are not merely reactive but also proactive in creating social resilience that can prevent exploitation from its early stages.